2022
DOI: 10.1186/s13071-022-05414-4
|View full text |Cite
|
Sign up to set email alerts
|

dynamAedes: a unified modelling framework for invasive Aedes mosquitoes

Abstract: Mosquito species belonging to the genus Aedes have attracted the interest of scientists and public health officers because of their capacity to transmit viruses that affect humans. Some of these species were brought outside their native range by means of trade and tourism and then colonised new regions thanks to a unique combination of eco-physiological traits. Considering mosquito physiological and behavioural traits to understand and predict their population dynamics is thus a crucial step in developing stra… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 130 publications
2
9
0
Order By: Relevance
“…This is likely due to the fact that during the rainy season, BG-GAT has to compete with the large number of larval breeding habitats present in the study localities, as shown by Wat'senga et al [12]. In Kinshasa, temperature is not a limiting factor in the development of both Aedes species [18], although temperature and humidity play critical roles in the population dynamics of both species by impacting Aedes mortality and, hence, pathogen transmission [19]. The differences in densities between the dry and rainy seasons seem to be the result of the rainfall and the presence of water-containing larval habitats.…”
Section: Discussionmentioning
confidence: 75%
See 1 more Smart Citation
“…This is likely due to the fact that during the rainy season, BG-GAT has to compete with the large number of larval breeding habitats present in the study localities, as shown by Wat'senga et al [12]. In Kinshasa, temperature is not a limiting factor in the development of both Aedes species [18], although temperature and humidity play critical roles in the population dynamics of both species by impacting Aedes mortality and, hence, pathogen transmission [19]. The differences in densities between the dry and rainy seasons seem to be the result of the rainfall and the presence of water-containing larval habitats.…”
Section: Discussionmentioning
confidence: 75%
“…Larval source management is one of the key interventions, whereas adult Aedes control strategies are primarily considered for outbreak control. However, the epidemiological impact of adult vector control is uncertain (see e.g., [18]). In Kinshasa, adult vector control methods should target mosquitoes outdoors due to the marked exophagic and exophilic behavior of the two vector species Ae.…”
Section: Discussionmentioning
confidence: 99%
“…Unlike correlative models, process-based models are usually independent of geographical observations of the taxa under investigation. These typically express biological (or other) processes by a mathematical equation (e.g., ordinal differential equation or matrix population models) relating an indicator of the process (e.g., a lifehistory trait such as the number of offspring) to different factors affecting its performance (e.g., environmental conditions) (Da Re et al, 2022;Kearney et al, 2010). For instance, Larter et al (2017) showed how a single plant functional trait (xylem resistance to cavitation) displayed a strong statistical relationship with its species distribution in relation to aridity across the climatic range of the species.…”
Section: Discussionmentioning
confidence: 99%
“…Unlike correlative models, process-based models are usually independent of geographical observations of the taxa under investigation. These typically express biological (or other) processes by a mathematical equation (e.g., ordinal differential equation or matrix population models) relating an indicator of the process (e.g., a life history trait such as the number of offsprings) to different factors affecting its performance (e.g., environmental conditions) (Kearney et al, 2010;Da Re et al, 2022). For instance, Larter et al (2017) showed how a single plant functional trait (xylem resistance to cavitation) displayed a strong statistical relationship with its species distribution in relation to aridity across the climatic range of the species.…”
Section: Discussionmentioning
confidence: 99%